Forbidden planet [videorecording (DVD)] - Wilcox, Fred M.; Pidgeon, Walter, 1897-1984; Francis, Anne, 1930-2011; Nielsen, Leslie, 1926-2010; Block, Irving; Adler, Alan J. (MGM/UA Home Video : Turner Entertainment Co., 1997)
The far-off star Altair-IV, occupied by two lone inhabitants and Robie the Robot, is visited by a search party from Earth.